(untitled) (Revista INTEREDU11, 2021)
This article presents the analysis of arguments for the development of IT projects with free software, in the Spanish Public Education, through the study of three emblematic cases. The arguments were obtained during the qualitative analysis process of the primary data, provided through the application of a set of semi-structured interviews to the project management teams, and so, analyzed and structured, all based on a dynamic categorization. This process required the use of five categories for their justification, which correspond to the following five points of view: technical, ethical, economic, strategic-institutional and pedagogical. The main findings relate to the variety of options for software adaptation, multilingual development, cross-platform mode availability, development and technical support with local human capital, legal download, copy, installation, study and modification for anyone, plus the low-cost development and basically zero-cost for any user, among others.